Optimal control of vaccine distribution in a rabies metapopulation model - Erika Asano; Louis J. Gross; Suzanne Lenhart; Leslie A. Real (Mathematical Biosciences and Engineering)
We consider an SIR metapopulation model for the spread of rabiesin raccoons. This system of ordinary differential equations considers subpop-ulations connected by movement. Vaccine for raccoons is distributed throughfood baits. We apply optimal control theory to find the best timing for dis-tribution of vaccine in each of the linked subpopulations across the landscape.This strategy is chosen to limit the disease optimally by making the numberof infections as small as possible while accounting for the cost of vaccination.